2013
DOI: 10.1021/ci300502h
|View full text |Cite
|
Sign up to set email alerts
|

Fragment-Based Drug Discovery Using a Multidomain, Parallel MD-MM/PBSA Screening Protocol

Abstract: We have developed a rigorous computational screening protocol to identify novel fragment-like inhibitors of N5-CAIR mutase (PurE), a key enzyme involved in de novo purine synthesis that represents a novel target for the design of antibacterial agents. This computational screening protocol utilizes molecular docking, graphics processing unit (GPU)-accelerated molecular dynamics and Molecular Mechanics/Poisson-Boltzmann Surface Area (MM/PBSA) free energy estimations to investigate the binding modes and energies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 61 publications
(115 reference statements)
0
18
0
Order By: Relevance
“…Although MM‐P(G)BSA methods have been used successfully in both virtual screening and lead optimization programs, it has been shown that the results are sensitive to atomic charges, simulation length, entropy calculations, and sampling protocols which can lead to dramatic differences in affinity predictions using the same study system . Studies have also suggested that prediction results of MM‐GBSA methods might be influenced by radii settings .…”
Section: Introductionmentioning
confidence: 99%
“…Although MM‐P(G)BSA methods have been used successfully in both virtual screening and lead optimization programs, it has been shown that the results are sensitive to atomic charges, simulation length, entropy calculations, and sampling protocols which can lead to dramatic differences in affinity predictions using the same study system . Studies have also suggested that prediction results of MM‐GBSA methods might be influenced by radii settings .…”
Section: Introductionmentioning
confidence: 99%
“…Methods that require long serial trajectories, such as those built upon molecular dynamics [23], [24], require frequent CPU-GPU communication. This in turn leads to latency that limits the speedup achievable through GPU computing.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of biomolecular modeling tasks have been adapted for GPU processing, from carrying out quantum calculations to calculating electrostatic surface potentials to stochastic modeling of chemical kinetics and molecular dynamics [17][22]. GPU computing has also been used to speed up certain other structure-based docking tools [23][29].…”
Section: Introductionmentioning
confidence: 99%
“…2A). 15, 16 This analysis showed that His298, Phe392, Thr302, Phe390, Val270, Pro272, Thr300, Gly391 and His333 contribute to TLM binding.…”
mentioning
confidence: 93%